2008
DOI: 10.1007/s10350-008-9348-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Surgical Recurrence after Ileocolic Resection of Crohn's Disease

Abstract: Both a family history of inflammatory bowel disease and smoking at the time of the initial ileocolic resection are associated with an increased risk of a second ileocolic resection. Postoperative prescription of immunomodulators is associated with a reduced risk of surgical recurrence. This study supports the concept that both genetic and environmental factors influence the risk of surgical recurrence of ileal Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 27 publications
7
54
0
1
Order By: Relevance
“…Moreover, extraintestinal manifestations, such as arthralgia or lesions affecting eyes, skin, and mouth, might also support the Regarding the phenotypes classified according to the Montreal system, the distribution of age of onset in our patients was similar to that of Western populations. 21 However, the distribution of disease location was quite different in our patients from studies in Western populations [21][22][23] or Hong Kong. 24 Our data showed that more than half of our patients had ileocolic disease (L3), whereas disease limited to the colon (L2) was not common (13.7%).…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, extraintestinal manifestations, such as arthralgia or lesions affecting eyes, skin, and mouth, might also support the Regarding the phenotypes classified according to the Montreal system, the distribution of age of onset in our patients was similar to that of Western populations. 21 However, the distribution of disease location was quite different in our patients from studies in Western populations [21][22][23] or Hong Kong. 24 Our data showed that more than half of our patients had ileocolic disease (L3), whereas disease limited to the colon (L2) was not common (13.7%).…”
Section: Discussionmentioning
confidence: 54%
“…[17][18][19] Family history of IBD in the present study was found to affect the operative recurrence time. Although the incidence of a family history of CD was similar between the two groups, a family history of IBD was associated with late rather than early operative recurrence.…”
Section: Discussionmentioning
confidence: 66%
“…4,12 There is conflicting data on whether small bowel disease, ileocolic disease, or colonic disease has the higher likelihood of recurrence. 11,12,14 Newer data also suggest that patients carrying mutations in the NOD2/CARD 15 gene have a higher risk of postoperative recurrence. 15 Clearly, some patients will have a higher risk of disease recurrence compared to other patients and such patients should be identified for aggressive postoperative medical management.…”
Section: Risk Factors For Postoperative Recurrencementioning
confidence: 94%
“…15 Clearly, some patients will have a higher risk of disease recurrence compared to other patients and such patients should be identified for aggressive postoperative medical management. However, the precise factors involved in postoperative recurrence of CD remain unclear, 11,12,16,17 although it is likely that a combination of environmental, genetic, and disease treatment factors affect the timing and severity of disease recurrence in any individual patient.…”
Section: Risk Factors For Postoperative Recurrencementioning
confidence: 98%